The Analysis of Taboo Words in Euphoria Season 1 Episode: Shook Ones PT. II - Viola Sondea Sinaga; Romel Noverino (JEdu: Journal of English Education, 2023)
In expressing emotive feelings, people tend to use bad language by uttering taboo words. Although taboo words are considered offensive and are prohibited in society, taboo words are still uttered by some people and are not even censored in movies. This research aims to identify the types of taboo words and to identify the function of taboo words uttered in Euphoria Season 1 Episode: Shook Ones Pt. II. The data of this research are in the form of sentence or dialogue containing taboo words which are found in the transcript of the series. This research applied descriptive qualitative method. The data were classified based on Battistella’s theory of types of taboo words and Wardhaugh’s theory of functions of taboo words. The result of the research shows that there are 107 taboo words found in 78 dialogues in this episode. There are four types of taboo uttered by the characters in the episode, namely obscenity, profanity, vulgarity and epithets. Based on the data analysis, obscenity becomes the most frequently uttered, and vulgarity as well as epithets become the rarely uttered with the same frequency. In analyzing the functions of taboo words, all of the four functions of taboo words are found in the result of the research, namely to draw attention, to show contempt, to be aggressive or provocative, and to mock authority. The most frequently used is the function to draw attention, and the least one is the function to mock authority.